2010
DOI: 10.3354/meps08790
|View full text |Cite
|
Sign up to set email alerts
|

Stable isotope analysis reveals habitat partitioning among marine mammals off the NW African coast and unique trophic niches for two globally threatened species

Abstract: Stable isotope abundances of carbon (δ 13 C) and nitrogen (δ 15 N) in the bone of 13 species of marine mammals from the northwest coast of Africa were investigated to assess their positions in the local trophic web and their preferred habitats. Also, samples of primary producers and potential prey species from the study area were collected to characterise the local isotopic landscape. This characterisation indicated that δ 13 C values increased from offshore to nearshore and that δ 15 N was a good proxy for tr… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

6
54
0
2

Year Published

2012
2012
2023
2023

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 47 publications
(62 citation statements)
references
References 62 publications
6
54
0
2
Order By: Relevance
“…A multivariate cluster analysis was performed to explore the intrinsic pattern of the δ 13 C and δ 15 N values of females, including also the isotopic signature of 3 marine mammal species from Pinela et al (2010) to be used as a reference for neritic and oceanic stable isotope ratios. A nonparametric Mann-Whitney U-test was used to compare the δ …”
Section: Discussionmentioning
confidence: 99%
See 3 more Smart Citations
“…A multivariate cluster analysis was performed to explore the intrinsic pattern of the δ 13 C and δ 15 N values of females, including also the isotopic signature of 3 marine mammal species from Pinela et al (2010) to be used as a reference for neritic and oceanic stable isotope ratios. A nonparametric Mann-Whitney U-test was used to compare the δ …”
Section: Discussionmentioning
confidence: 99%
“…Fidelity to foraging grounds and dietary specialization is also evident among the neritic foragers identified here, as they exhibited a much higher variability in their stable isotope ratios than that of oceanic foragers. However, even within oceanic foragers there is remarkable variability, for example a group of 6 turtles were extremely depleted in 13 C and 15 N and, hence, likely to exploit the most distant feeding grounds from mainland Africa (Pinela et al 2010).…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…In marine systems, several studies have shown that there are consistent differences between the isotopic composition of animals living in pelagic vs. benthic environments, and among estuarine, nearshore and offshore environments (France 1995, Kurle & Gudmundson 2007, Cherel & Hobson 2007, Newsome et al 2010, Ohizumi & Nobuyuki 2010. Therefore, the use of stable isotopes can help identify the utilization of different habitats by species (Das et al 2003, Capelli et al 2008, Gross et al 2009, Newsome et al 2010, Pinela et al 2010. Additionally, by using this technique, it can be possible to determine if sympatric species explore the same resources and occupy the same trophic level (Cherel et al 2008, Newsome et al 2010.…”
Section: Introductionmentioning
confidence: 99%